Effectiveness of application of telemonitoring of blood pressure in patients with normal weight and overweight - Inna Berdnyk (Bogomolets National Medical University, 2021)
The article summarizes the arguments and counterarguments within the scientific discussion on the methods of diagnosing hypertension and features of blood pressure control. The main purpose of this study is to evaluate the effectiveness of blood pressure monitoring in patients with normal weight and overweight and to determine their level of adherence to treatment. The relevance of the study about this pathology is that hypertension is the leading cause of cardiovascular disease and premature death worldwide. The prevalence of hypertension among the adult population is 30-45%, in 2018 the number of patients with hypertension in the world was about 1.38 billion, with more than 165 million living in Central and Eastern Europe. Systematization of literature data showed that despite the widespread use of antihypertensive drugs, only about 30% of patients have optimal blood pressure. The methodology of the study is to evaluate the use of telemedicine technologies for self-monitoring of blood pressure in patients with normal weight and overweight and increase their compliance. The study was conducted in Kyiv, Ukraine during 2018-2020, and included 111 patients aged 18 to 65 years with a previously diagnosed hypertension. By randomization, they were divided into the main group (used blood pressure monitoring) and the control group (used office and home blood pressure monitoring). The article presents the results that in the patients of the main group at the end of the study the average daily systolic and diastolic blood pressure were significantly lower in comparison with both the initial level of the group and in comparison with the control. The baseline adherence to treatment in patients in both groups was low. However, at the end of the study, the adherence of patients in the main group to treatment increased by 40.3%, while in the control group no significant changes were detected. In addition, a correlation was found between patients with overweight and less adherence to regular medication, more frequent skipping of the drug and self-withdrawal with improvement compared to patients with normal body weight. It was also noted that the patients in the main group at the end of the study significantly reduced the level of anxiety compared with the control. The study empirically confirms and theoretically proves that the use of blood pressure telemonitoring can be considered as an alternative to the standard approach that increases adherence to treatment. The results of the study will be useful for primary care physicians, cardiologists, therapists.